The gender-race intersection and the 'sheltering-effect' of public-sector employment. (February 2021) - Mandel, Hadas; Semyonov, Moshe
Abstract: Seeking to understand the role played by labor market structure in affecting economic inequality, we examine the extent to which the public sector, as compared to the private sector, differentially employs and rewards women, Blacks and subgroups classified by race and gender (e.g., Black women, Black men). Analyzing data from the American Community Survey (2014–2015), we find that public-sector employment is more attractive for Blacks than for women; Blacks' odds of becoming public-sector employees are much higher than those of Whites, regardless of gender. No evidence was found for the argument that gender interacts with race in affecting the tendency to work in the public sector. As for wages, despite recent trends pointing to a decline in the advantages of the public sector for Blacks, it is still found to be more protective of Blacks, men and women alike. The meaning of the findings and their implications are discussed in light of structural barriers of gender and race inequality.